Landscape study on open access monographs: Policies, funding and publishing in eight European countries - Stern, Niels (Septentrio Conference Series, 2017)
Watch the VIDEO here. The monograph is one of the most prestigious scholarly publication outlets – a hallmark of reputation, a tool for career progression and a means of disseminating fundamental ideas of scholarship. Open access policies from funders, publishers and institutions have been relatively quiet on monographs and other long form publications, predominantly focusing on journals. However the beginnings of a transition to open access for monographs has commenced and there are several projects and initiatives exploring and experimenting in this area. I would like to report on an in-depth study covering eight European countries (including Norway, Finland and Denmark) that compares and contrasts the monograph publishing landscape, where policy on OA for monographs stands, and how OA monograph publishing is now moving quickly forward. Librarians, who are increasingly being asked to support OA initiatives may be interested in the developments reported here. The primary goal of the Landscape study was to assemble comparable data and analysis from Germany, Finland, Denmark, United Kingdom, The Netherlands, Norway, Austria and France. This includes the costs of OA books; the fees charged for OA books; the range of non-BPC models; the adoption of OA policies for books by funders (both public and private), universities, and publishers. An overview of OA book publishing along with a review of policies and mandates highlights the various national differences as well as similarities. While including examples from all eight countries the presentation will pay special attention to developments and experiments in the Nordic countries. Financial support for the study came from Knowledge Exchange, the Current Research Information System in Norway (CRIStin), the Austrian Science Fund (FWF), and the French library consortium Couperin. Eelco Ferwerda (OAPEN), Frances Pinter (KU Research) and Niels Stern (Nordic Council of Ministers) are joint Principal Investigators, with support from Lucy Montgomery (KU/Curtin University) and Ronald Snijder (OAPEN).